Economical and Managerial Competencies of Bachelors in Mechanical Engineering; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 19 : Lifelong Wellbeing in the World (WELLSO 2016) - Lizunkov V. G. Vladislav Gennadyevich; Marchuk V. I. Veronika Ivanovna; Malushko E. Yu. Elena Yurievna; Maletina O. A. Oksana Andreevna; Zavyalova A. V. Anastasia Vyacheslavovna (2017, 2017)
Title screen